A chemical evaluation of the feed and fertilizing value of the feelings of banana (musa sapoientum variety compressa). - Moscoso, Allan Dino
The potential of the peelings of unripe banana (Musa sapientum variety compressa) as animal feed was determined by proximate analysis. The anlysis showed that banana contain 19.9 moisture, 8.64 ash, 9.76 ether extract, 10.00 crude protein, 52.53 nitrogen-free extract. Banana peelings, therefore, can be used as a feed supplement when it is properly processed and combined wit other feed ingredients. The potential of the peelings of unripe banana as an organic soil ameliorant was also determined through analysis of total nitrogen, total phosphorus as P2O5, and total potassium as K2O. The sample was composted for four weeks using Trichoderma as activator, prior to chemical analysis. The result showed that the decomposed banana peelings contain 1.42 total nitrogen, 10.8 total phosphorus and 1.30 total potassium. The result indicated that composted banana peelings contain the essential plant nutrients with phosphorus as the highest in value. As an organic matter, the compost will improve the physical properties of the soil. (NOTE: CORRECTION P2O5 & K2O).